Krishna
0

Step 1: Consider a right angle triangle

              NOTE:  Right angle triangle ABC with right angle is at B

                        


Step 2: Write the Pythagoras theorem to the triangle.

            NOTE:   AC^2 = AB^2 + BC^2


Step 3: Dividing each term by hypotenuse.(AC) and simplify

            EXAMPLE:   \frac{AC^2}{AC^2} = \frac{AB^2}{AC^2} + \frac{BC^2}{AC^2}


                                  (\frac{AC}{AC})^2 = (\frac{AB}{AC})^2 + (\frac{BC}{AC})^2     


                             (\frac{AC}{AC})^2 = (\frac{opposite}{hypotenuse})^2 + (\frac{adjacent}{hypotenuse})^2       


                               1^2 = (\sin \theta)^2 + (\cos \theta)^2   

            

                                  \sin^2 \theta + \cos^2 \theta = 1